Application of carboxylic acid-functionalized of graphene oxide for electrochemical simultaneous determination of tryptophan and tyrosine in milk - Fooladi, E. (Springer Nature, 2020)
Abstract: In this work, a new method for the simultaneous determination of tryptophan (Trp) and tyrosine (Tyr) in milk has been reported. Trp and Tyr are essential amino acids in human nutrition, but their electrochemical signal overlapped. For solve this problem, we developed modified Screen Printed Carbon Electrode (SPCE) with Graphene OxideâCOOH/Chitosan (GOâCOOH/Chitosan) electro-deposition. The morphology and electrochemical performance of modified electrode were characterized by scanning electron microscopy, energy dispersive spectrometry, FT-IR, electrochemical impedance spectroscopy and cyclic voltammetry. The electrochemical simultaneous determination of Trp and Tyr has been investigated by using differential pulse voltammetry. The carboxylic acid functionalized GO modified SPCE was utilized to catalyze the oxidation of Trp and Tyr. Compared with SPCE/GO/Chitosan and SPCE/Chitosan sensor, the new sensor has enhanced sensitivity, low detection limit and high selectivity. In addition, the SPCE/GOâCOOHâChitosan sensor enhanced separation of the oxidation peak of Tyr and Trp and showed a remarkable increase in peak current for electro-active compounds, thus, it can be used for simultaneous voltammetric determination. Under the optimized experimental conditions, a linear correlation between oxidation peak current and concentration of Tyr and Trp in the ranges 0.1â60Â ÂµM and 0.4â40Â ÂµM with a detection limit of 0.05Â ÂµM (S/N = 3) and 0.1Â ÂµM (S/N = 3) were achieved, respectively. Finally, the proposed electrochemical sensor was applied for quantification of Tyr and Trp in milk samples, where standard solutions were spiked to the milk samples and recoveries were obtained. Graphic abstract: Figure not available: see fulltext. Â© 2020, Springer Nature Switzerland AG.